THE TRANSLATION OF ENGLISH PARTICIPIAL ADJECTIVES IN “HARRY POTTER AND THE CHAMBER OF SECRET” - Adlina, Nuri (Journal of Language and Literature, 2017)
This research investigated the translation of English participial adjectives in Harry Potter and the Chamber of Secret novels and their translations in Indonesian. The aims of the research are to find out what participial adjectives used in the Harry Potter and the Chamber of Secret, to identify how participial adjectives in Harry Potter and the Chamber of Secret translated into Indonesian and to find out whether the messages in the source text are transferred in Harry Potter and the Chamber of Secret. The method employed in this research is qualitative. The findings revealed there are157 participial adjectives. It contains of 112 participial adjectives with –ing form and 45 participial adjectives with –ed form. Moreover the strategies which found out as follows :79 data (50%) used literal (syntactic strategy), 73 (47%) data used unit shift (syntactic strategy), 2 (1%) data used transposition (syntactic strategy), 3 (2%) data used explicitness change (pragmatic strategy) According to the data analysis, the most dominate strategy is literal. The result of study showed that from all 157 data, the messages in the SL are transferred in the target language. By using the theories of good translation, the messages of PA in the SL are transferred and can be understood in the TL. Keywords: Participial adjectives, Strategies, Translation